A flow blurring nozzle design for combustion in a closed system. (25th February 2018) - Pongvuthithum, Radom; Moran, James; Sankui, Tanakarn
Abstract: The objective of this research is to design an atomizer for liquid hydrocarbon combustion in meso-scale applications. The goal is to use the atomizer in a closed meso-scale combustion chamber. For these applications, the heat output desired is between 1 and 4 kW (2–8 ml/min of gasoline). This heat will ultimately be used to power a meso scale energy conversion device. A high pressure atomizer, such as the fuel injectors used in automotive engines do not function well at the low fuel flow rates required here. Instead, this research is focused on a new nozzle design based on a relatively new phenomena called flow blurring. Flow blurring is defined as the generation of small turbulence scales in a liquid from a singular back-flow pattern of a gas. It has a high vaporization efficiency, operates within a wide flow rate range and is inexpensive. There are a few studies of atomizers based on the flow blurring phenomena. These studies only consider an original flow blurring nozzle with a single air supply. However, at the target flow rate, the standard flow blurring nozzle cannot be used since the exit velocity will be much higher than the flame speed. Thus, sustainable combustion is not possible. To solve the problem, a new dual air supply nozzle with diffuser is proposed. A design framework and experimental results of the proposed nozzle are presented. The experimental data demonstrate that the proposed nozzle greatly improves combustion stability over the original nozzle and can achieve clean and stable combustion for a wide range of fuel flow rates. This new design of a flow blurring nozzle can also be applied to other potential applications requiring small droplets at low flow rates.